Desenvolvimento e avaliação de nova configuração geométrica de rotor para aerador de solo sob pastagens degradadas - Bender, André Rogério Kinalski (2020)
Aeration and incorporation of fertilizers in agricultural soil are alternatives for restoring and/or the productivity increase of a pasture, the one is first fundamental for the development of plants. Nevertheless, a lack of equipment is observed in the agricultural machinery market, regarding this function. Thus, the objective of this work was to develop and evaluate a new geometric configuration of a soil aerator machine for use in degraded pastures and other agricultural crops. The methodology applied to the development of the project is based on the phase model of the Modelo de Referência para o Processo de Desenvolvimento de Máquinas Agrícolas of Romano (2013), applying activities from the phases: Informational, Conceptual, Preliminary and Detailed. The main definitions of the machine design, as well as of the soil aeration mechanism, were carried out through the collection of information in which it was, seeking the definition of design specifications and the creation of solution principles for the elementary functions of the machine. The results of the preliminary project phase allowed the manufacture of the ground aerator machine prototype and rotor variants for evaluation. The prototype was subjected to functional tests and the execution of comparative experimental evaluation in the field. Conditions “before” and “after” the soil mobilization were evaluated by the functional principle proposed for the aeration mechanism and its comparison variants. The results of the field evaluations showed that the proposed new geometric configuration presents different levels of soil aeration compared to the commercial rotor.